2015
DOI: 10.1902/jop.2014.140266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scaling and Root Planing on Clinical Response and Serum Levels of Adipocytokines in Patients With Obesity and Chronic Periodontitis

Abstract: Patients with obesity and CP presented lower reductions in PD than patients without obesity with CP at 6 months after SRP. Furthermore, the treatment did not affect the circulating levels of leptin and adiponectin in any group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 29 publications
5
77
2
Order By: Relevance
“…There were significant changes in mild (≤3 mm) and moderate (4-6 mm) PPD and CAL in both groups, whereas severe (>6 mm) PPD and CAL did not exhibit significant improvement at any time-point in either group. These findings are consistent with those of recent studies, which reported persistent residual periodontal pockets of >6 mm, even after NSPT, in obese participants (27,39). These data suggest that obesity compromises periodontal healing, especially in deep periodontal pockets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were significant changes in mild (≤3 mm) and moderate (4-6 mm) PPD and CAL in both groups, whereas severe (>6 mm) PPD and CAL did not exhibit significant improvement at any time-point in either group. These findings are consistent with those of recent studies, which reported persistent residual periodontal pockets of >6 mm, even after NSPT, in obese participants (27,39). These data suggest that obesity compromises periodontal healing, especially in deep periodontal pockets.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first randomized clinical trial that included a control group that did not receive any form of periodontal treatment (negative control), which allowed us to estimate the real magnitude of the effect of NSPT in obese CP patients. Previous studies compared the effects of periodontal treatment in obese and nonobese participants with CP and found improved clinical periodontal characteristics at follow-up in both groups after full-mouth scaling and root planing (19,(25)(26)(27)(28). In the present study, participants in the control group were assured that they would be given periodontal treatment at the end of the trial.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding is in agreement with the results of Ongoz Dede et al and Duzagac et al (52,53). Gonçalves et al showed that reduced probing depth was lower in obese patients with CP compared with non-obese individuals with CP six months after SRP treatment; no difference was observed for three months (13,54).…”
Section: Discussionsupporting
confidence: 91%
“…sig. )Gonçalves et al 2015 [31]Total number of patients:39Without obesity: 21With obesity: 18Age:Without obesity: 48.4(±9.5)With obesity: 48.8 (±5.9)p-value= 0.85 (n. sig.…”
Section: Methodsmentioning
confidence: 99%